2015
DOI: 10.1016/j.jecp.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility in young children: General or task-specific capacity?

Abstract: a b s t r a c tCognitive flexibility is the ability to adapt to changing tasks or problems. To test whether cognitive flexibility is a coherent cognitive capacity in young children, we tested 3-to 5-year-olds' performance on two forms of task switching, rule-based (Three Dimension Changes Card Sorting, 3DCCS) and inductive (Flexible Induction of Meaning-Animates and Objects, FIM-Ob and FIM-An), as well as tests of response speed, verbal working memory, inhibition, and reasoning. Results suggest that cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 77 publications
(91 reference statements)
4
69
4
3
Order By: Relevance
“…Specifically, attention control lies at the bottom of the hierarchy because it is very basic, keeping mental focus on target against salient but irrelevant object characteristics [Diamond, 2013]. Flexibility in shifting across stimuli or responses according to complementary goals is the next level in the hierarchy because it brings mental focus under the executive control of the thinker, allowing deployment of mental or behavioral plans [Deak & Wiseheart, 2015]. Working memory resides higher because it involves, in addition to an executive program, information to be stored and related storage and recall processes [Baddeley, 2012;Cowan, 2016].…”
Section: Is There a Developmental G?mentioning
confidence: 99%
“…Specifically, attention control lies at the bottom of the hierarchy because it is very basic, keeping mental focus on target against salient but irrelevant object characteristics [Diamond, 2013]. Flexibility in shifting across stimuli or responses according to complementary goals is the next level in the hierarchy because it brings mental focus under the executive control of the thinker, allowing deployment of mental or behavioral plans [Deak & Wiseheart, 2015]. Working memory resides higher because it involves, in addition to an executive program, information to be stored and related storage and recall processes [Baddeley, 2012;Cowan, 2016].…”
Section: Is There a Developmental G?mentioning
confidence: 99%
“…This is a question that itself is open to discussion. Some have suggested that set-shifting does not represent a global trait that can be captured by a single measure (Deák & Wiseheart, 2015). Of course, if there is no general switching mechanism, then frequent language switching could not possibly benefit task switching.…”
Section: A General Switch Mechanism?mentioning
confidence: 99%
“…Resisting distraction from information unrelated to the current task is an essential aspect of goal‐directed behavior. Distraction errors occur on executive function tasks in infants (Diamond, ), toddlers (Zelazo, Reznick, & Spinazzola, ), preschoolers (Blakey et al., ; Brooks, Hanauer, Padowska, & Rosman, ; Chevalier & Blaye, ; Deák & Wiseheart, ), and adolescents (Crone, Ridderinkhof, Worm, Somsen, & van der Molen, ), though we still have little understanding of why they occur. Distraction errors arise when children select a response that is not correct according to either the current rule or the previous rule.…”
mentioning
confidence: 99%